2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20181813
|View full text |Cite
|
Sign up to set email alerts
|

A study on spectrum of periorbital dermatoses in a tertiary centre

Abstract: <p class="abstract"><strong>Background:</strong> To study the spectrum of periorbital dermatoses in patients of both genders irrespective of age and identify any underlying etiology.</p><p class="abstract"><strong>Methods:</strong> A clinico-epidemiological study of periorbital dermatoses was done in all patients with skin lesions in and around the both eyes who visited our outpatient department. Digital photographs will be taken for all the patients with periorbital d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
3
2
1
Order By: Relevance
“…In our study peri orbital tumours were the commonest (34.7%), amongst which skintags were the most commonly observed (16%) followed by seborrheic keratosis (13.3%). Pigmentation (24%) was the second most common periorbital dermatoses observed with melasma being the commonest among them (10.7%) These results are similar to the studies done by Nalini P et al, Indradevi et al, Besra et al 20,2,18 In our study, 9.3% of the patients presented with periorbital infections and periorbital dermatitis was seen in 24% of the patients which was comparable to the studies done by Indradevi et al, Besra et al 2,18…”
Section: Discussionsupporting
confidence: 91%
“…In our study peri orbital tumours were the commonest (34.7%), amongst which skintags were the most commonly observed (16%) followed by seborrheic keratosis (13.3%). Pigmentation (24%) was the second most common periorbital dermatoses observed with melasma being the commonest among them (10.7%) These results are similar to the studies done by Nalini P et al, Indradevi et al, Besra et al 20,2,18 In our study, 9.3% of the patients presented with periorbital infections and periorbital dermatitis was seen in 24% of the patients which was comparable to the studies done by Indradevi et al, Besra et al 2,18…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed the predominant involvement of <10y age group; 25.9% of patients, in contrast to other studies [8][9][10][11][12][13]96-101 which reported the prevalence of an older age group. This variation may be related to the sample size and the differences in the demographic characteristics between India and Iraq, where these studies are conducted.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the female patients 57.9% preponderates the males' 42.1% with a female to male ratio of 1.3:1. These facts were closely comparable to other reported studies [8][9][10][11][12][13][14]96-101. The reasons for sex related disparities remain unknown, and maybe multifactorial.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations